UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SISTEM PENDINGIN DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL PADA SISWA KELAS X PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN SMK NEGERI 1 MONDOKAN SRAGEN TP 2011/2012 - Nugroho, Deny Setya (Jurnal Nosel, 2013)
The purpose of this research are: (1) To determine the level of students' understanding of the material cooling system, (2) To determine the use of multimedia technologies will have an impact in the field of education, so that it must be addressed by creating a new instructional media or develop existing there, (3) To determine the effect of the use of audio-visual media to the increased activity and student learning outcomes in SMK Negeri 1 MondokanSragen. This type of research is Classroom Action Research (CAR) conducted in two cycles, each cycle consisting of: (1) action planning, (2) implementation of actions and observations, and (3) Reflection. Subject implementing measures in this study is an observer and subject teachers Cooling System, while class X-3 Light Vehicle Engineering SMK Negeri 1 MondokanSragen number of 32 students as subjects receiving action. Data collection methods used were observation, interviews, documentation and field notes. The technique of data analysis is descriptive comparative, quantitative description and qualitative description that consists of data collection, data reduction, and data presentation, drawing conclusions. The results show that this class action: (1) The utilization of audio-visual media can enhance learning in class X activity Skills Program Light Vehicle Engineering SMK Negeri 1 MondokanSragen TP 2011/2012. It is based on data and research findings in the field in the form of written data derived from observations and dialogue. The application of this learning model to increase student activity, the initial conditions of 22%, in the first cycle increased to 63% and on the second cycle increased to 78%. Assessment is based on aspects of student activity 4 things are, spirit, partnership, argued and asked, (2) use of audio-visual media learning can improve learning outcomes motor cooling system in class X Light Vehicle Technical Skills Program SMK Negeri 1 Mondokan TP 2011/2012 . From the empirical data demonstrates the use of audio-visual media to improve student learning outcomes. At baseline the minimum 30, maximum 90, and the average value of 60 with 53% mastery class. In the first cycle 35 minimum value, maximum value of 92 and an average value of 68,3 with 66% mastery class. In the second cycle 50 minimum value, maximum value of 98 and an average value of 77,3 with 81% mastery class .